Understanding the needs and perspectives of young adults with recent suicidal ideation: insights for suicide prevention - Looijmans, Milou; Elzinga, Elke; Popma, Arne; van Bergen, Diana; Gilissen, Renske; Mérelle, Saskia (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Suicide rates among adolescents and young people are increasing, especially in Western countries. Suicidal ideation often precedes suicide attempts and suicide. Yet, research involving individuals with lived experience in suicide prevention, especially among young adults, remains scarce. Understanding their needs is crucial for effective interventions. This qualitative study aims to explore the needs and perspectives of young adults with lived experience to provide tailored recommendations for suicide prevention. Methods Semi-structured interviews were carried out with 19 young adults who had experienced suicidal ideation within the past two years. Open-ended questions addressed the needs for help and support regarding suicide prevention. Data was thematically analyzed and, through an iterative process involving discussion among all authors, categorized into six themes. Results The results indicated needs around more openness and understanding of suicide among the general public, advocating mental health education starting from a young age, reducing barriers in mental health care such as long waiting lists and enhancing informal support systems by facilitating online and offline peer connections. Participants also highlighted contemporary concerns such as social welfare, academic pressure, and social media as significant needs in the current time. Conclusion This study highlights the necessity for comprehensive suicide prevention approaches catering to the diverse needs of young adults with recent suicidal ideation. It highlights the urgency of societal awareness, early mental health education, and improved access to services. Informal support networks and addressing societal stressors are also deemed crucial. Structural changes are urged to create supportive environments.